DEVELOPING STUDENTS’ TRANSLANGUAGING COMPETENCE IN EFL CLASSROOMS (SCIENCE TIME JOURNAL, 2026)
This article examines the development of students’ translanguaging competence in English as a Foreign Language (EFL) classrooms within the context of Uzbekistan. Translanguaging is viewed as an effective pedagogical approach that enables learners to utilize their full linguistic repertoire, including Uzbek, Russian, and English, to enhance comprehension and communication. The study explores the theoretical foundations of translanguaging and analyzes its role in improving students’ communicative competence, particularly in speaking, writing, and listening skills. Furthermore, the paper presents practical strategies for implementing translanguaging in Uzbek educational settings, such as code-switching practices, multilingual tasks, collaborative learning activities, and scaffolding techniques. The findings indicate that translanguaging not only facilitates language acquisition but also increases students’ confidence, critical thinking abilities, and intercultural communicative competence. The article concludes with methodological recommendations for teachers to effectively integrate translanguaging practices into EFL instruction in Uzbekistan.